Macrophage migration inhibitory factor modulates proliferation, cell cycle, and apoptotic activity in head and neck cancer cell lines - Kusumawadee Utispan; Sittichai Koontongkaew (Elsevier, 2021)
Background/purpose: Macrophage migration inhibitory factor (MIF) is a multifunctional cytokine that contributes to the progression of several cancers. MIF overexpression has been reported in head and neck squamous cell carcinoma (HNSCC) patients. However, the exact role of MIF in HNSCC is not fully understood. Our aim was to evaluate the amount of secreted MIF and the role of MIF in the proliferation, cell cycle, and apoptosis in HNSCC cell lines. Materials and methods: Genetically matched HNSCC cell lines derived from primary (HN18 and HN30) and metastatic sites (HN17 and HN31) from the same patient were used in this study. The MIF levels in conditioned media from the HNSCC cell lines were evaluated using ELISA. The HNSCC cell lines were treated with recombinant MIF at concentrations 25, 50 and 100 ng/ml, and cell proliferation was evaluated by MTT assay. A proliferative dose of MIF was used to treat the cells then, cell cycle, and apoptotic status were determined by flow cytometry. Results: The HNSCC-secreted MIF concentration ranged from 49.33 to 973 pg/ml. Exogenous MIF (25 ng/ml) significantly increased HN18, HN30, and HN31 cell proliferation. Moreover, MIF induced cell cycle progression and inhibited apoptosis in these cells. However, MIF did not affect growth or apoptosis in HN17 cell. Conclusion: MIF secreted from the HNSCC cell lines were evaluated. Exogenous MIF promotes various effects on proliferation, cell cycle, and apoptosis in HNSCC cells.